Domain-specific and unspecific reaction times in experienced team handball goalkeepers and novices - Helm, Fabian; Reiser, Mathias; Munzert, Jörn; Justus Liebig University Giessen (My University, 2016)
In our everyday environments, we are constantly having to adapt our behavior to changing conditions. Hence, processing information is a fundamental cognitive activity, especially the linking together of perceptual and action processes. In this context, expertise research in the sport domain has concentrated on arguing that superior processing performance is driven by an advantage to be found in anticipatory processes (see Williams et al., 2011, for a review). This has resulted in less attention being paid to the benefits coming from basic internal perceptual-motor processing. In general, research on reaction time (RT) indicates that practicing a RT task leads to an increase in processing speed (Mowbray and Rhoades, 1959; Rabbitt and Banerji, 1989). Against this background, the present study examined whether the speed of internal processing is dependent on or independent from domain-specific motor expertise in unpredictable stimulus response tasks and in a double stimulus response paradigm. Thirty male participants (15 team handball goalkeepers and 15 novices) performed domain-unspecific simple or choice stimulus response (CSR) tasks as well as CSR tasks that were domain-specific only for goalkeepers. As expected, results showed significantly faster RTs for goalkeepers on domain-specific tasks, whereas novices RTs were more frequently excessively long. However, differences between groups in the double stimulus-response paradigm were not significant. It is concluded that the reported expertise advantage might be due to recalling stored perceptual-motor representations for the domain-specific tasks, implying that experience with (practice of) a motor task explicitly enhances the internal processing of other related domain-specific tasks.
Keywords: reaction times; task specificity; perception; action; cognition; ddc:796